Perbandingan Kebijakan dan Penegakan Hukum Terkait Cornering The Market (Negara Indonesia dan Amerika Serikat) - Enjela Novia (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
In general, products that are bought and sold in the capital market are company ownership rights and company debt statements. Buyers in the capital market can be individuals, institutions or organizations who are willing to set aside funds to invest in the capital market. In securities trading transactions in the capital market, there are two forms of legal protection, namely, preventive legal protection and repressive legal protection through Law Number 8 of 1995 concerning Capital Markets and the connection with the existence of BAPEPDAM (Capital Market Supervisory Agency) which has changed its name to Authority. Financial Services (OJK). However, in practice there are still crimes involved, one of which is cornering the market The cause of cornering the market in the capital market begins with widening stock spreads and increasing share price volatility. However, the Capital Market Law still has weaknesses in terms of handling practices in the form of cornering the market, so it is still considered inadequate. And can optimize the imposition of prison sentences on perpetrators of cornering the market in the capital market as has been implemented by the United States.